Effect of nature and pressure of ambient environments on the surface morphology, plasma parameters, hardness, and corrosion resistance of laser-irradiated Mg-alloy. (24th April 2015) - Dawood, Asadullah; Bashir, Shazia; Akram, Mahreen; Hayat, Asma; Ahmed, Sajjad; Iqbal, Muhammad Hassan; Kazmi, Ali Hassan
Abstract The influence of nature and pressure of ambient environment on the surface modification, plasma parameters, hardness, and corrosion resistance of Mg-alloy has been investigated. Nd: YAG laser (1064 nm, 10 ns, 25 mJ) at a fluence of 1.3 J cm−2 has been employed as an irradiation source. Targets of Mg-alloy were exposed in the ambient environments of argon (Ar), neon (Ne), and helium (He) at pressures ranging from 5 to 760 Torr. Scanning electron microscope has been employed to investigate the surface morphology of the irradiated targets. It reveals the formation of cavities, cones, droplets, ripples, and islands on the surface of the irradiated sample. Laser-induced breakdown spectroscopy technique was employed to measure electron temperature (Te) and electron number density (Ne) of Mg-alloy. The value of electron temperature ranges from 6628 to 12, 855 K, whereas the value of electron number density varies from 5.4 × 1017 to 19.2 × 1017 cm−3. The maximum Te and Ne are observed in Ar and minimum in case of He. It was also revealed that both the surface morphology and plasma parameters are strongly dependent upon nature and pressure of environmental gases. The maxima of Te is achieved at a pressure of 10 Torr for all the three ambient environments that is, Ar, Ne, and He; whereas maxima of Ne is achieved at different pressures, that is, at 760 Torr for Ar, at 200 Torr for Ne, and at 50 Torr for He. The hardness and corrosion resistance of irradiated Mg-alloy have been explored using Vickers Micro-hardness tester and Potentio-dynamic polarization technique, respectively. It was investigated that as compared with un-irradiated target, the hardness as well as corrosion resistance of the laser-irradiated target has been increased significantly in all environments. Plasma parameters, mechanical, and electrical properties of laser-irradiated Mg-alloy have been correlated with induced surface modifications and are strongly influenced by environmental conditions.